Game Theory Application on Funding Strategy PT. Bank Syari’ah Mandiri and PT. Bank BNI Syari’ah Facing the Competition of Islamic Banking Industry in Indonesia - Wijanarko, T; Fajar Cahyono, E (KnE Social Sciences, 2019)
This study aims to show the application of game theory on the funding strategy of PT. Bank Syari’ah Mandiri and PT. Bank BNI Syari’ah in facing competition of syariah banking industry in Indonesia. The approach used is descriptive quantitative by using payoff matrix analysis technique in game theory between PT. Bank Syari’ah Mandiri and PT. Bank BNI Syari’ah as research subject and funding strategy as object of research and DPK, hajj fund, number of customer as indicator of payoff. The results showed that the Nash Ekuilibrium and the Prisoner’s Dilemma were not found in this game. Dominant strategy that get the highest payoff from each banks is a strategy to increase the promotion and marketing of haji cheap more aggressive to increase core deposit in anticipation of the decrease of funds due to the establishment of Hajj Financial Management Agency (BPKH) with 32,1 score for PT. Bank Syari’ah Mandiri and mass-funding strategy in partnership with BNI in the form of agency cooperation / Sharia Services Bank and synergize with micro outlet for marketing DPK with 25,4 score for PT. Bank BNI Syari’ah. Keywords: Game Theory, Strategy, Bank Funding, Islamic Bank